Análise da atividade da enzima delta-aminolevulinato desidratase (d-ALA-D) no diabetes mellitus e no hipotireoidismo - Souza, João Baptista D'andrea (2004)
The activity of Delta-Aminolevulinate Dehydratase (d-ALA-D) was analyzed in patients suffering from diabetes mellitus and primary hypothyroidism. Five groups of patients were studied: compensated diabetes mellitus, non-compensated diabetes mellitus, compensated hypothyroidism, non-compensated hypothyroidism and control group. The analysis of d-ALA-D in these groups showed the following results: the activity of d-ALA-D on non-compensated diabetes mellitus decreased comparing to the control group, to the compensated diabetes mellitus group. The activity of d-ALA-D on non-compensated hypothyroidism increased compared to the control group and also to non-compensated hypothyroidism. In vitro analyses of the drugs used by the patients suffering diabetes mellitus (metformin, chlorpropamide, glibenclamide, glimepiride) and the drug used by the patients suffering primary hypothyroidism (thyroxine) were fulfilled to verify some change in the activity of d-ALA-D, and the findings showed that there was not any changes on d-ALA-D activity. Metals may interfere in the action of d-ALA-D. Consequently,the quantity of metals (lead, zinc, copper) present in the patients blood was measured. One observed that the amount of those metals was not different, from a statistical, among the groups. Therefore, we can conclude that the activity of d-ALA-D increased in the group of non-compensated hipothyroidism and decreased in the non-compensated diabetes, and may be it could be related to the complications observed in such pathologies